2022
DOI: 10.1111/jbi.14517
|View full text |Cite
|
Sign up to set email alerts
|

Do endemic mushrooms on oceanic islands and archipelagos support the theory of island biogeography?

Abstract: Aim Terrestrial plant species on islands have a long history of study to determine how they evolved and what explains their levels of endemicity, but studies on fungi are lacking. Here, we examine: (1) how percent endemism of non‐lichenized class Agaricomycetes; hereafter, ‘mushrooms’ compares to angiosperms, ferns, bryophytes and lichens from oceanic islands/archipelagos; (2) whether endemic mushrooms evolved from an ancestor diversifying into multiple species after island colonization (cladogenesis) or over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Studies of island biogeography provide valuable insight into the underlying patterns that govern microbial diversity ( 1 , 2 ). However, there is a lack of information on the diversity and distribution of soil microbes on remote and inaccessible islands.…”
Section: Announcementmentioning
confidence: 99%
“…Studies of island biogeography provide valuable insight into the underlying patterns that govern microbial diversity ( 1 , 2 ). However, there is a lack of information on the diversity and distribution of soil microbes on remote and inaccessible islands.…”
Section: Announcementmentioning
confidence: 99%
“…The application of the term endemic for fungi is problematic, although some cases have been demonstrated over time. The study of fungal endemism, especially on islands, is often hampered by insufficient data making it difficult to apply the term endemic and evaluate case studies (Stallman et al 2022). In the State of Biodiversity in Italy, published in 2005 (Blasi et al 2005), 56 fungal species are reported as possible endemics.…”
Section: Introductionmentioning
confidence: 99%